2022
DOI: 10.1088/2053-1591/ac6cd0
|View full text |Cite
|
Sign up to set email alerts
|

Surface states induced weak anti-localization effect in Bi0.85Sb0.15 topological single crystal

Abstract: We report, an experimental evidence of surface states (SS) driven magneto-transport in a Bi0.85Sb0.15 single crystal. Detailed high field (up to 12T) and low temperature (down to 2K) magneto-transport measurements are been carried out on the studied Bi0.85Sb0.15 single crystal. The phase, composition and Raman modes are studied through X-ray diffraction, Energy dispersive X-ray, and Raman spectroscopy. The obtained crystal shows non-saturating magnetoresistance (≈ 4250%) at 2K and 12T, along with the existence… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 54 publications
2
1
1
Order By: Relevance
“…However, Sultana et al found an increase in the frequency of the A 1g with Sb content [56], in contrast with our work and the early studies [54,55]. We note that Kumar et al [59] found lower frequencies for both modes in the case of Bi 0.85 Sb 0.15 alloys than in our work and in other works. This might be explained by the heating of the sample due to too large laser power used in their experiments.…”
Section: Raman Scatteringcontrasting
confidence: 99%
“…However, Sultana et al found an increase in the frequency of the A 1g with Sb content [56], in contrast with our work and the early studies [54,55]. We note that Kumar et al [59] found lower frequencies for both modes in the case of Bi 0.85 Sb 0.15 alloys than in our work and in other works. This might be explained by the heating of the sample due to too large laser power used in their experiments.…”
Section: Raman Scatteringcontrasting
confidence: 99%
“…The decrease of α as the temperature increases is consistent with the previous research on other topological materials [39,45]. According to the Nyquist theory, the relation between L f and the temperature caused by electron-electron (e-e) interactions should solely be L T 1 2 µ f -/ for a quasi-2D system [43,46]. In our case, however, L f is not proportional to T .…”
Section: Weak Anti-localizationsupporting
confidence: 91%
“…The temperature-dependent factor α shall be equal to 1/2 for a 2D conducting system. However, as shown in figure 4(b), the relatively large α indicates the contribution from the bulk and that from the surface states are both involved in the transport event [40][41][42][43][44]. The decrease of α as the temperature increases is consistent with the previous research on other topological materials [39,45].…”
Section: Weak Anti-localizationsupporting
confidence: 88%
“…16, which are indexed to the (003) plane of (Bi,Sb) alloy resulting from the in situ alloying of Bi and Sb. These two adjacent peaks are ascribed to the alloying of Bi/Sb in arbitrary ratios so that there is a slightly difference in interplanar spacing . The above mentioned results indicate the gradual phase transitions from the K x (Bi-Sb) 2 S 3 to K x S and (Bi,Sb) alloy.…”
Section: Resultsmentioning
confidence: 70%